Consensus opinion on immune-mediated cytopenias after hematopoietic cell transplant for inherited metabolic disorders - Gupta, Ashish O. (Bone Marrow Transplant, 2021)
Hematopoietic stem cell transplantation (HCT) has been increasingly used for patients with inherited metabolic disorders (IMD). Immune mediated cytopenias (IMCs) after HCT, manifesting as hemolytic anemia, thrombocytopenia, and/or neutropenia, are recognized as a significant complication in this patient population, yet our understanding of the incidence, risk factors, and pathophysiology is currently limited. Review of the published literature demonstrates a higher incidence in younger patients who undergo HCT for a nonmalignant disease indication. However, a few reports suggest that the incidence is even higher among those with IMD (incidence ranging from 10 to 56%). This review summarizes the literature, provides an approach to better understanding of the possible etiology of IMCs, and proposes a diagnostic and management plan for patients with IMD who develop single or multi-lineage cytopenias after HCT.